Eksplorasi faktor-faktor penentu kompetensi profesional guru MTs: Perspektif supervisi, pengalaman, dan disiplin kerja - Mursyidah, Any; Tsurayya, Layli (Indonesian Journal of Educational Management and Leadership, 2024)
Purpose − The purpose of this research was to determine (1) the contribution of principals academic supervision, teaching experience, and work discipline on the professional competencies of MTs teachers. 2) the contribution of school principals' academic supervision to the professional competence of MTs teachers. (3) the contribution of teaching experience to the professional competencies of MTs teachers. (4) the contribution of work discipline to the professional competence of MTs teachers. Method − This study was correlative descriptive study with quantitative approach followed. The population of this study were 220 MTs teachers in Buleleng regency. The samples of this research were taken by proportional cluster random sampling of 135 MTs teacher. Data collection used questionnaire for the school supervisor’s academic supervision variables, teaching experience, work discipline and teacher professional competence. In this study, validity testing of the instrument was using person’s product moment correlation while the reliability test used Alpha Cronbach. Data analysis used by the researcher was multiple regression analysis.. Findings − Based on the result of the study, it has shown that: 1) There was a significant contribution between of headmaster academic supervision variables, teaching experience and work dicipline simultaneous to the professional competence of MTs teachers in Buleleng Regency. 2) There was a significant positive contribution between the principals academic supervision on the teacher’s professional competence of MTs teachers in Buleleng Regency. 3) There was a significant positive contribution between teaching experience on the teacher professional competence of MTs teachers in Buleleng Regency. 4) There was a significan positive contribution between work discipline on teacher professional competence of MTs teachers in Buleleng Regency.